PALMsiever: a tool to turn raw data into results for single-molecule localization microscopy. (31st October 2014) - Pengo, Thomas; Holden, Seamus J.; Manley, Suliana
Abstract : During the past decade, localization microscopy (LM) has transformed into an accessible, commercially available technique for life sciences. However, data processing can be challenging to the non-specialist and care is still needed to produce meaningful results. PALMsiever has been developed to provide a user-friendly means of visualizing, filtering and analyzing LM data. It includes drift correction, clustering, intelligent line profiles, many rendering algorithms and 3D data visualization. It incorporates the main analysis and data processing modalities used by experts in the field, as well as several new features we developed, and makes them broadly accessible. It can easily be extended via plugins and is provided as free of charge open-source software. Contact: thomas.pengo@gmail.com